النظام القانوني للمضايق الدولية – مضيق هرمز نموذجا - خولة ذيب; أحلام عادل (My University, 2026)
Abstract This study focuses on the one hand to highlight the role of the Strait of Hormuz on the energy security in the Persian Gulf, as well as the importance of strategic location, which is a strategic hub in the region, which led to the attraction of the big powers greedy for taking over it, and the appearance of the declared and its hidden intentions. it hired media strategy and mechanisms pour into the new economic interests template in the first place, without taking into account the specificity of the place and its sensibility, the thing that has made the region a place to settle scores between rival forces, was the bigest impact of it to ask a lot of questions, most notably about the strategic role of the Strait of Hormuz on the energy security in the Arabian Gulf region. On the other hand, the study is trying to confirm the importance of energy security as a criterion in the Gulf region and its relation to the Strait of Hormuz, which saw the region- particularly the Straits -of many of the transformations Associated with the security dimension of energy. And trying to interpret the attraction and repulsion between the controlling factors in the energy security of the main the actors in the region, due to the unrest and fluctuations in oil prices through supply and demand, and therefore the potential repercussions and implications for these interactions. ...................................... ملخص: تركز هذه الدراسة من جهة، على إبراز دور مضيق هرمز على الأمن الطاقوي في الخليج العربي، فضلا عن أهمية موقعه الاستراتيجي الذي يشكل محورا استراتيجيا للمنطقة، ما أدى إلى انجذاب القوى الكبرى الطامعة للاستيلاء عليه، وظهور النوايا المعلنة والخفية لها. إذ وظفت وسائل استراتيجية وآليات جديدة تصب في قالب مصالحها الاقتصادية بالدرجة الأولى، دون مراعاة لخصوصية المكان وحساسيته، الشيء الذي جعل من المنطقة مكان لتصفية الحسابات فيما بين القوى المتنافسة، فكان لها الأثر البالغ في طرح الكثير من التساؤلات، لعل أبرزها حول الدور الاستراتيجي لمضيق هرمز على الأمن الطاقوي في منطقة الخليج العربي. ومن جهة أخرى، تحاول الدراسة التأكيد على أهمية الطاقة كمحدد أمني في منطقة الخليج وارتباطها بمضيق هرمز، حيث شهدتا لمنطقة -وبالأخص المضيق- العديد من التحولات المرتبطة بالبعد الأمني للطاقة. وتحاول تفسير التجاذب والتنافر بين العوامل المتحكمة في الأمن الطاقوي للفواعل الرئيسية في المنطقة، جراء الاضطرابات والتذبذبات في أسعار النفط من خلال العرض والطلب، وبالتالي الانعكاسات والمحتملة والآثار المترتبة عن هذه التفاعلات. .................................... Résumé Cette étude vise d'une part à mettre en lumière le rôle du détroit d'Ormuz dans la sécurité énergétique du golfe Persique, ainsi que l'importance de sa position géographique, véritable pôle stratégique dans la région. Cela a attiré les convoitises des grandes puissances désireuses d'en prendre le contrôle, révélant leurs intentions déclarées et cachées. Elles ont employé une stratégie et des mécanismes médiatiques servant avant tout de nouveaux intérêts économiques, sans tenir compte de la spécificité et de la sensibilité des lieux. Cette situation a transformé la région en un terrain de règlement de comptes entre puissances rivales, soulevant de nombreuses interrogations, notamment sur le rôle stratégique du détroit d'Ormuz sur la sécurité énergétique de la région du golfe Arabique. D'autre part, l'étude cherche à confirmer l'importance de la sécurité énergétique comme critère fondamental dans la région du Golfe et sa relation avec le détroit d'Ormuz, qui a connu — en particulier au niveau du détroit — de nombreuses transformations liées à la dimension sécuritaire de l'énergie. Elle tente également d'analyser les dynamiques d'attraction et de répulsion entre les facteurs influençant la sécurité énergétique des principaux acteurs de la région, en raison des troubles et des fluctuations des prix du pétrole via l'offre et la demande, ainsi que les répercussions et implications potentielles de ces interactions.
Keywords: Keywords Strait of Hormuz- Strategic locations - International community - International waters.; الكلمات المفتاحية: مضيق هرمز، المواقع الاستراتيجية، المجتمع الدولي، المياه الدولية.; Mots-clés Détroit d'Ormuz - Positions stratégiques - Communauté internationale - Eaux internationales.